If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3.7 + t = 9.45 Solving 3.7 + t = 9.45 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-3.7' to each side of the equation. 3.7 + -3.7 + t = 9.45 + -3.7 Combine like terms: 3.7 + -3.7 = 0.0 0.0 + t = 9.45 + -3.7 t = 9.45 + -3.7 Combine like terms: 9.45 + -3.7 = 5.75 t = 5.75 Simplifying t = 5.75
| 6x+15y=4 | | kx-x=k^2-1 | | m+13.9=-5.3 | | 8=3.14 | | 3x+2x-5=13-2(x+2) | | 0.35(17-x)+x=0.40(17) | | 5+2x+6=17 | | b=95+(15+8)w | | 14-2(3x+6)=3x-(2x-16) | | -4n-18=16 | | 44.91=9g+3.69 | | .15(10-x)+x=0.40(10) | | 45=d^2 | | 4t^2-5t-60=0 | | -35=-22-w | | 5x+20=9x-53 | | 49x^3-9x=0 | | 8x-8y=32 | | 2y-4(6)=-12 | | 0.5+3=x-2 | | 23=14-x | | .15(8-x)+x=0.40(8) | | (2+i)z-3+2i=0 | | Y^2+2.5y-9=0 | | 2x-y-4=13 | | (80x+60y)-(2x+30y)= | | -7(u+4)=-3u-16 | | 3x+x=y-18 | | 9x+4x+2=8x+3+4x | | -9=-6+x | | .10(8-x)+x=0.40(8) | | 12-2t=1-t |